Physiological quality of zucchini seeds is positively affected by postharvest resting periods - Aguilar, Ariel Santivañez; Bardiviesso, Estefânia Martins; Vasques, Henrique; Acevedo, Andres Felipe Gaona; Cardoso, Antonio Ismael Inácio; Pelvine, Raíra Andrade; Leis, José Murillo Oliveira; Lemes, Ernane Miranda (Revista de Ciencias Agrícolas, 2024)
In fleshy fruit species such as those of the Cucurbitaceae plant family (e.g., zucchini), the storage or resting after harvest of the fruits enables the seeds to complete their maturation process, reaching maximum levels of germination and vigor. The proper resting period can allow early harvestings, improve the agronomic uses of the area, and reduce seed exposure to weathering and the attack of insects and microorganisms. This study evaluates zucchini seed quality after postharvest resting periods. Zucchini fruits harvested 63 days after transplanting were maintained for 0, 3, 6, 9, or 12 days before seed extraction. The percent of processed seeds (clean and whole seeds), the weight of 100 seeds, germination, first count in germination, germination speed index, electrical conductivity, nitrogen (N), and protein contents were evaluated. Data generally fitted positive linear regression models, increasing the weight of 100 seeds, percent of processed seeds, germination, vigor, seed N, and protein as the resting period after harvest (days) increases. Seed electrical conductivity decreased as days of postharvest rest increased. After the harvest of the zucchini fruits, the resting period positively affected the production of homogeneous and high-quality zucchini seeds.